Tactics of surgical treatment of the malignant heart tumors - R.M. Vitovskyi; V.V. Isaіenko; D.М. Dyadyun; V.F. Onishchenko; O.A. Pishchurin; I.V. Martyshchenko (Кардіохірургія та інтервенційна кардіологія)
The aim – to determine the features of surgical treatment of the malignant heart tumors, aimed at their most radical removal. Materials and methods. At the M.M. Amosov National Institute of Cardiovascular Surgery of NAMS of Ukraine, during the period 1970–2018 66 patients with malignant neoplasms of the heart of various types and localization were observed, which accounted 6.9 % of the total number of patients with heart tumors (n = 939). Results. Hospital mortality during the surgical treatment was 19.7 % (13 patients). Among 66 operations, 55 (83.3 %) were performed using artificial blood circulation, including 21 (3.8 %) conditionally radical cardiac surgeries with good hemodynamic effect. Conclusions. To achieve the conditional radicalism of the surgery and the maximum hemodynamic effect, it is necessary to use advanced techniques for reconstructing damaged cardiac structures in combination with active detoxification therapy and urgent chemotherapy.